Mitigating the costs of departure. Brain drain, disadvantage and fair burden-sharing - Alexandru Volacu; Vlad Terteleac (Ethics & Global Politics, 2021)
In this article we aim to assess how the negative effects of brain drain can be mitigated in a fair way. We particularly focus on the policies of extraterritorial taxation and temporary compulsory service for highly skilled migrants in developing countries, which are most thoroughly defended by Gillian Brock. We argue that while Brock is right in pressing for policies seeking to combat the damaging effects of brain drain, she fails to properly characterize the complex strands of disadvantage that run through this phenomenon, placing an unfair redistributive burden on highly skilled migrants. By contrast, we maintain that any fair distribution of such burdens can only flow from a comprehensive account of existing comparative disadvantages, without regard for migratory status. The resulting policy implications are that a considerable part of the tax burden required for mitigating brain drain should be borne by citizens of developed countries, and that compulsory service in developing countries should be rejected.